Flail Chest: Clinical Management, Nursing Interventions, and Radiological Assessment - Bokar, Elham Ahmad Mohammed; Abdulaziz Fahad Alamrani; Mariam Saud Alanazi; Hanan Saud Alanazi; Ahmad Talal Matar Almarshadi; Rawan Ayidh Alqahtani; Shahad Abdullah Alanazi; Mohammed Omar Mohammed Sultan; Nada Jaber Jaboor; Shouq Ali Mohammed Assiri; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Flail chest is a severe thoracic injury defined by fractures of multiple ribs in at least two locations, resulting in paradoxical chest wall motion and impaired ventilation. It most commonly arises from high-energy blunt trauma and is frequently associated with pulmonary contusions and multisystem injuries. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to provide an integrated overview of the etiology, epidemiology, pathophysiology, clinical assessment, radiologic evaluation, and management strategies for flail chest to guide effective multidisciplinary care. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive narrative review approach was used, synthesizing current trauma guidelines and contemporary evidence on diagnosis, imaging, respiratory support, analgesia, and surgical stabilization of rib fractures (SSRF). <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Findings indicate that flail chest significantly compromises respiratory mechanics, increases the risk of hypoxemia and pneumonia, and often necessitates hospitalization or mechanical ventilation. CT imaging provides the most accurate diagnosis. Optimal outcomes rely on multimodal analgesia, respiratory support, pulmonary hygiene, and selective early SSRF, which reduces ventilation duration, pneumonia rates, and hospital stay. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early recognition and individualized, multidisciplinary management substantially improve outcomes. Surgical stabilization is particularly beneficial in severe cases with persistent instability or ventilatory dependence.